2020
DOI: 10.1093/nar/gkaa1123
|View full text |Cite
|
Sign up to set email alerts
|

Bacterial tRNA 2′-O-methylation is dynamically regulated under stress conditions and modulates innate immune response

Abstract: RNA modifications are a well-recognized way of gene expression regulation at the post-transcriptional level. Despite the importance of this level of regulation, current knowledge on modulation of tRNA modification status in response to stress conditions is far from being complete. While it is widely accepted that tRNA modifications are rather dynamic, such variations are mostly assessed in terms of total tRNA, with only a few instances where changes could be traced to single isoacceptor species. Using Escheric… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
29
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 29 publications
(29 citation statements)
references
References 83 publications
(54 reference statements)
0
29
0
Order By: Relevance
“…Alternatively, METTL2B possibly needs other unknown co-factors in catalyzing tRNA modification. On the other hand, tRNA modification has been shown to be highly dynamic in response to various stimuli or stresses ( 33 , 34 ). It is possible that the m 3 C32 modification level is precisely balanced based on the expression level or ratio of METTL2A and METTL2B, which is regulated in a tissue- or cell-specific manner.…”
Section: Discussionmentioning
confidence: 99%
“…Alternatively, METTL2B possibly needs other unknown co-factors in catalyzing tRNA modification. On the other hand, tRNA modification has been shown to be highly dynamic in response to various stimuli or stresses ( 33 , 34 ). It is possible that the m 3 C32 modification level is precisely balanced based on the expression level or ratio of METTL2A and METTL2B, which is regulated in a tissue- or cell-specific manner.…”
Section: Discussionmentioning
confidence: 99%
“…S8, table S5). This enzyme is thought to reduce the immuno-stimulatory nature of bacterial tRNA, which is detected by Toll-like receptors (TLR7) of the mammalian innate immune system (67,68). While plasmids in some pathogens are known to facilitate bacterial evasion of mammalian immune system by regulating surface proteins (69), the overwhelming prevalence of tRNA modification enzymes in our data suggests the likely presence of a previously unappreciated role for plasmids to increase the fitness of their bacterial hosts against the survey of the human immune system.…”
Section: Conserved Backbones Are Recombined With Variable Cargo In Plasmid Systemsmentioning
confidence: 99%
“…In general, it was shown that the degree of modification varies with growth and stress conditions, e.g. growth temperature or starvation ( 77 , 78 ). However, it was recently shown that the C m 32 modification of initiator tRNA fMet in E. coli is not affected by different growth conditions and temperatures ( 77 ).…”
Section: Resultsmentioning
confidence: 99%
“…growth temperature or starvation ( 77 , 78 ). However, it was recently shown that the C m 32 modification of initiator tRNA fMet in E. coli is not affected by different growth conditions and temperatures ( 77 ).…”
Section: Resultsmentioning
confidence: 99%